Oxytocin exerts harmful cardiac repolarization prolonging effects in drug-induced LQTS. (June 2022) - Kreifels, Paul; Bodi, Ilona; Hornyik, Tibor; Franke, Gerlind; Perez-Feliz, Stefanie; Lewetag, R.; Moss, Robin; Castiglione, Alessandro; Ziupa, David; Zehender, Manfred; Brunner, Michael; Bode, Christoph; et al.
Abstract: Background: Oxytocin is used therapeutically in psychiatric patients. Many of these also receive anti-depressant or anti-psychotic drugs causing acquired long-QT-syndrome (LQTS) by blocking HERG/IKr . We previously identified an oxytocin-induced QT-prolongation in LQT2 rabbits, indicating potential harmful effects of combined therapy. We thus aimed to analyze the effects of dual therapy with oxytocin and fluoxetine/risperidone on cardiac repolarization. Methods: Effects of risperidone, fluoxetine and oxytocin on QT/QTc, short-term variability (STV) of QT, and APD were assessed in rabbits using in vivo ECG and ex vivo monophasic AP recordings in Langendorff-perfused hearts. Underlying mechanisms were assessed using patch clamp in isolated cardiomyocytes. Results: Oxytocin, fluoxetine and risperidone prolonged QTc and APD in whole hearts. The combination of fluoxetine + oxytocin resulted in further QTc- and APD-prolongation, risperidone + oxytocin tended to increase QTc and APD compared to monotherapy. Temporal QT instability, STVQTc was increased by oxytocin, fluoxetine / fluoxetine + oxytocin and risperidone / risperidone + oxytocin. Similar APD-prolonging effects were confirmed in isolated cardiomyocytes due to differential effects of the compounds on repolarizing ion currents: Oxytocin reduced IKs, fluoxetine and risperidone reduced IKr, resulting in additive effects on IKtotal -tail. In addition, oxytocin reduced IK1, further reducing the repolarization reserve. Conclusion: Oxytocin, risperidone and fluoxetine prolong QTc / APD. Combined treatment further prolongs QTc/APD due to differential effects on IKs and IK1 (block by oxytocin) and IKr (block by risperidone and fluoxetine), leading to pronounced impairment of repolarization reserve. Oxytocin should be used with caution in patients in the context of acquired LQTS.